Dynamic surface potential decay tendency of cellular polypropylene after temperature control corona process. (April 2015) - Zhang, J. W.; Chen, X.; Belouadah, R.; Zhou, T. C.; Yin, C.; Shi, Y. T.; Niu, Y. Z.
<x content-type="archive" xml:space="preserve">Abstract</x> In order to evaluate the temperature influence on the charge storage property of cellular polypropylene, especially for its surface charge deposition, the tested polymers were charged through a special corona triode system. A temperature controlling corona point-to-plane unipolar poling system was used in the material treatment process of the cellular polymer. In this paper, the dynamic behaviour of surface potential has been recorded and analysed. In addition, the physical mechanism of unipolar corona has been used to analyse the surface modification of the tested polymers specifically, which is closely related to surface charge deposit and chemical bonds generated in the poling procedure. The results of this paper play a significant role in the understanding of the charge storage mechanism of the foam polymers and their future application in the fields of energy harvester, sensors and actuators, etc.